The seasonal characteristics of cloud condensation nuclei (CCN) in the arctic lower troposphere - Chang Hoon Jung; Young Jun Yoon; Hyo Jin Kang; Yeontae Gim; Bang Yong Lee; Johan Ström; Radovan Krejci; Peter Tunved (Tellus: Series B, Chemical and Physical Meteorology, 2018)
Cloud Condensation Nuclei (CCN) concentration and aerosol size distributions in the Arctic were collected during the period 2007–2013 at the Zeppelin observatory (78.91° N, 11.89° E, 474 masl). Annual median CCN concentration at a supersaturation (SS) of 0.4% show the ranges of 45 ∼ 81 cm−3. The monthly median CCN number density varied between 17 cm−3 in October 2007 and 198 cm−3 in March, 2008. The CCN spectra parameters C (83 cm−3) and k (0.23) were derived. In addition, calculated annual median value of hygroscopicity parameter is 0.46 at SS of 0.4%. Particle number concentration of accumulation mode from aerosol size distribution measurements are well correlated with CCN concentration. The CCN to CN>10 nm (particle number concentration larger than 10nm in diameter) ratio shows a maximum during March and minimum during July. The springtime high CCN concentration is attributed to high load of accumulation mode aerosol transported from the mid-latitudes, known as Arctic Haze. CCN concentration remains high also during Arctic summer due to the source of new CCN through particle formation followed by consecutive aerosol growth. Lowest aerosol as well as CCN number densities were observed during Arctic autumn and early winter when aerosol formation in the Arctic and long-range transport into the Arctic are not effective.